Fluorimetric reusable polymeric sensor for hydrogen sulfide detection - ÇUBUK, SONER; KAHRAMAN, MEMET VEZİR (My University, 2023)
In this study, with the help of reactive monomers, crosslinkers, and photoinitiator that detect H2S in various matrices, an H2S sensitive fluorescence sensor polymerizes under ultraviolet (UV) light was developed. To this goal, a polymeric membrane was prepared, and the characterization of the membrane was carried out with Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) methods. Afterward, appropriate conditions were identified, the excitation wavelength was determined as 370 nm, and the emission wavelength was determined as 425 nm. It was established that the fluorescence intensity of the prepared polymeric membrane decreased in the presence of H2S. A detailed analysis was executed to determine the sensor's most suitable pH value and time. It was found that the optimum pH was 8.0, and the optimal duration was 15 s. It has been calculated that the linear range of the developed method is 2.19× 10–8– 6.25× 10–7 M, and the detection limit (LOD) is 7.37× 10–9 M. The effect of some possible interfering ions was investigated, and it determined that the sensor had excellent selectivity. In addition, the sensor used to determine H2S can be used at least 100 times. The recovery percentages were 102.1%–103.2%, and 104.6%, using tap water samples. In terms of providing reliable, fast results, high sensitivity, reusable, low cost, and ease of use, the developed fluorimetric sensor, compared to standard methods, has become more advantageous.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; CHEMISTRY; MULTIDISCIPLINARY SCIENCES; Kimya (çeşitli); Genel Kimya; Multidisipliner; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Multidisciplinary; Physical Sciences; Fluorimetric sensor; Photo-curing; Polymeric membrane; Selective H2S determination